Notational singles match analysis of male badminton players who participated in the African Badminton Championships - Abdullahi, Y.; Coetzee, B. (International Journal of Performance Analysis in Sport, 2017)
Purposes of this study were firstly, to determine the notational singles match analysis results of male badminton players and secondly, to determine relationships between notational singles match analysis determined strokes and foot movements in male badminton players, who participated in the African Badminton Championships. Twenty male singles matches from the team and individual events of the 2014 All Africa Badminton Championships were recorded live via video cameras and analysed using the Dartfish video analysis software package. Average match duration (1470.4 s), real time (432.9 s) and percentage of real time played (29.8%), number of rallies per match (68.4) and shots per rally (6.5) were calculated. Average shots per rally were found to be 6.5 and the work density, .4. Average stroke frequency per match was: drive - 122.1, clear - 118, smash - 56.2, net strokes - 54.3, drop-shot - 24.2 and the round-the-head stroke - 1.2. Foot movements delivered the following average results per match: chasse-step - 174.6, shuffle - 161.7, split-step - 61.6, half-lunge - 52.20, forward-lunge - 46.1 and scissors kick - 38.3. Significant Spearman Rank Correlation Coefficients existed between various foot movements and strokes. The study confirmed the applicability of computerised notational analyses in determining singles badminton match characteristics.